Language Variations in Describing Nutrition and Hydration Interventions in State Physician Orders for Life Sustaining Treatment Forms and the Implications for Advanced Dementia Patients - Sarah Rebecca Stephen (Palliative Medicine Reports)
Background: Research suggests that language can impact medical decision-making, but few studies exist describing the variations in language to describe end-of-life nutrition and hydration interventions. The language contained in the Physician Orders for Life Sustaining Treatment (POLST) form varies across states, but this variation has not yet been fully analyzed. This investigation has implications for communicating with surrogates about the insertion of feeding tubes in advanced dementia patients, a common procedure in this population despite its potentially high risks and low benefits. Objective: Identify and analyze the variations in language related to end-of-life nutrition and hydration interventions in state POLST forms. Design: Descriptive study. Measurements: The most up-to-date POLST forms for each of the 50 US states and the District of Columbia as of August 2022 were analyzed for their descriptions of end-of-life nutrition and hydration interventions. Results: Fifty out of 51 (98%) forms referenced nutrition and/or hydration interventions. Four main modifiers of the word “nutrition” and/or “hydration” were identified: artificial (32%), artificially administered (56%), medically administered (14%), and assisted/medically assisted (18%). Forty-eight (96%) forms indicated an explicit option to forgo feeding tubes, and all of these forms described doing so with negatively valenced language. Conclusions: The language describing end-of-life nutrition and hydration interventions and feeding tubes in state POLST forms is insufficiently specific and varies significantly across the country. These terms are at best ambiguous and at worst imply incorrect information. More precise language may assist in the difficult discussion between physicians and surrogates about inserting feeding tubes in advanced dementia patients.